Analisis Butir Soal Ujian Nasional Matematika SMP Tahun Ajaran2015/2016 ditinjau dari Aspek Kognitif TIMSS - Rohmah, Indah Fitri Zakiyah; , Prof.Dr.Budi Murtiyasa,M.Kom (2017)
The national exam as an integrator of the nation as well as a reflection of the quality of education in Indonesia. But on the other hand the study of assessment of the Trends in Mathematics and Science Study (TIMSS) Indonesia often are currently down. This study aimed to analyze the national exam mathematics junior high school 2015/2016 in terms of cognitive aspects TIMSS. The research is a qualitative targets are national exam mathematics junior high school 2015/2016. Data were analyzed using content analysis to analyze any items to measure the achievement of the cognitive aspects of the matter of the Mathematics National Examination 2015-2016. The results of this study showed that the percentage of 25% was obtained for the cognitive aspects of knowing (knowledge). This percentage is smaller than that has been targeted by the TIMSS 2015 by 35%. Percentage of 42.5% was obtained for the cognitive aspects of applying (the application). It TIMSS 2015 exceeded expectations by 40%, or 2.5% higher than expectations. Percentage of 32.5% was obtained for cognitive reasoning (reasoning), or 7.5% greater than the expected target at 25% . And it can be concluded that the national exams for junior high school 2015/2016 school year has not yet reached the desired target by TIMSS due the cognitive aspects of knowing the percentage is lower than expected TIMSS as well as cognitive aspects of cognitive reasoning applying and obtaining a greater percentage than expected TIMSS.